Mathematical modelling of carbon capture in a packed column by adsorption. (15th November 2020) - Myers, T.G.; Font, F.; Hennessy, M.G.
Graphical abstract: Highlights: Rigorous derivation of the equations describing adsorption in a packed column. Standard errors in the literature are identified. The first analytical solutions for concentration and amount of adsorbate. Explicit expressions for time of first breakthrough and adsorbed mass. Recommendations to improve carbon capture technologies. Abstract: A mathematical model of the process of carbon capture in a packed column by adsorption is developed and analysed. First a detailed study is made of the governing equations. Due to the complexity of the internal geometry it is standard practice to average these equations. Here the averaging process is revisited. This shows that there exists a number of errors and some confusion in the standard systems studied in the literature. These errors affect the parameter estimation, with consequences when the experimental set-up is modified or scaled-up. Assuming, as a first approximation, an isothermal model the gas concentration equation is solved numerically. Excellent agreement with data from a pressure swing adsorption experiment is demonstrated. A new analytical solution (valid away from the inlet) is obtained. This provides explicit relations for quantities such as the amount of adsorbed gas, time of first breakthrough, total process time and width and speed of the reaction zone, showing how these depend on the operating conditions and material parameters. The relations show clearly how to optimise the carbon capture process. By comparison with experimental data the analytical solution may also be used to calculate unknown system parameters.